THE BUKHARA PERFORMANCE STYLE IS A FACTOR IN THE DEVELOPMENT OF MORAL QUALITIES OF TEENAGERS - Samiyeva Mehriniso Azimovna; G’aybullayev Quvonchbek G’olibovich (Academia Science Repository, 2023)
Education of students' moral qualities in the process of music culture lessons of university schools requires continuous musical-pedagogical activity based on a long-term systematized and clear plan.